Ideas in transition. The work of social scientists associated with the Centro de Estudios de Estado y Sociedad (1983-1990) (Quinto Sol, 2021)
The processes of change of political regime entail moments of opening towards the debate and the elaboration of proposals for the new State under construction. In such context it was usual to see the proliferation of spaces for the development of studies and knowledge aimed at contributing to public policy. Women and feminists joined these spaces to demonstrate, from their professions, the conditions of inequality in which the female gender developed, an element that is not admissible in a regime with democratic claims. In this context, this article -after making an approach to the Argentine political transition and the development of the women's and feminist movement- analyzes the main theoretical and, therefore, political concerns of women and feminists associated with the Centro de Estudios de Estado y Sociedad during the first democratic government (1983-1990) after the end of Argentina's dictatorship.
Keywords: political transition; social scientists